A new genus and two new species of cave-dwelling cyclopoids (Crustacea, Copepoda) from the epikarst zone of Thailand and up-to-date keys to genera and subgenera of the Bryocyclops and Microcyclops groups - Boonyanusith, Chaichat; Sanoamuang, La-orsri; Brancelj, Anton (European Journal of Taxonomy, 2018)
Two obligate cave-dwelling species of cyclopoid copepods (Copepoda, Cyclopoida) were discovered inside caves in central Thailand. Siamcyclops cavernicolus gen. et sp. nov. was recognised as a member of a new genus. It resembles Bryocyclops jankowskajae Monchenko, 1972 from Uzbekistan (part of the former USSR). It differs from it by (1) lack of pointed triangular prominences on the intercoxal sclerite of the fourth swimming leg, (2) mandibular palp with three setae, (3) spine and setal formulae of swimming legs 3.3.3.2 and 5.5.5.5, respectively, and (4) specific shape of spermatophore. Metacyclops thailandicus sp. nov. resembles M. cushae Reid, 1991 from Louisiana (USA). It differs from it by (1) distal segment of the endopod of the fourth swimming leg with one apical spine, (2) the fifth swimming legs with one broad segment, (3) the spine formula of the distal segment of the exopod of the swimming legs 3.4.3.3, and (4) well developed anal operculum reaching articulation with caudal rami. Detailed descriptions of the habitats of the new species and up-to-date keys to the genera and subgenera of the Bryocyclops and Microcyclops groups are provided, along with an updated list of obligate groundwater species of Copepoda in Southeast Asia.